Prehistoric Peoples of South Florida. - McGoun, William (University of Alabama Press, 1993)
To many people in South Florida, an "oldtimer" is someone who has lived there for more than five years. Prehistoric Peoples of South Florida considers the culture history of the real South Florida "oldtimers" dating from 10,000 B.C. through the invasion by Europeans and analyzes the ways in which they adapted to their environment through timeor caused their environment to adapt to them. South Florida is a biological island, its plant communities circumscribed by the southern limits of frost. Its peoples were distinct from those to the north and were less studied by scholars.